Good neurological recovery after rescue thrombolysis of presumed pulmonary embolism despite prior 100 minutes CPR - Wu, Jiang-Ping; Gu, Dan-Yan; Wang, Sheng; Zhang, Zhen-Jun; Zhou, Jian-Cang; Zhang, Rui-Feng (Journal of Thoracic Disease, 2014)
We reported the case of a 70-year-old man who was admitted to neurologic wards for recurrent syncope for 3 years. Unfortunately, just 2 hours after his admission, he suddenly collapsed and failed to return of spontaneous circulation (ROSC) after a 100-minute standard cardiopulmonary resuscitation (CPR). Fortunately, he was timely suspected to have pulmonary embolism (PE) based on his sedentary lifestyle, elevated D-dimer and markedly enlarged right ventricle chamber on bedside echocardiography. After a rescue thrombolytic alteplase therapy, he was successfully resuscitated and good neurological recovery was achieved.